The role of renewable energy sources in Hungarian electricity production - Bozsik, Nándor; Bozsik, Norbert (Acta Carolus Robertus, 2024)
In the article, the sources of Hungarian electricity consumption was analyzed, as well as the composition and concentration of production. On the consumer side, the annual peak consumption trend of gross electricity was investigated, which also included a regression analysis of consumption. The data used for the analysis come from the databases of Eurostat, the Hungarian Central Statistical Office, the Hungarian Energy and Utilities Regulatory Office (MEKH) and the Hungarian Electricity Industry Transmission Controller (MAVIR). In Hungary, the sources of electricity consumption are domestic electricity generating plants, consumers producing from renewable sources and imported electricity. Hungary’s electricity production based on nuclear and fossils, At the same time, electricity produced from renewable energies increased significantly, which can be attributed to the remarkable increase in solar energy production. In the last period, a significant proportion of the demand for electricity came from imports, while domestic production increased to a negligible extent. Hungary - with the exception of Slovenia - trades electricity with all neighboring countries.